SISTEM INFORMASI PENILAIAN PROPOSAL SKRIPSI BERBASIS WEB DI FAKULTAS TEKNOLOGI INFORMASI UNIVERSITAS ISLAM KALIMANTAN MUHAMMMAD ARSYAD AL BANJARI BANJARMASIN - Silvia Ratna (Universitas Lambung Mangkurat, 2020)
Implementation of the final project or thesis for students is a tiered process and bound to one another. Starting from the stage of proposal submission, proposal presentation, research implementation, report making up to thesis examination students. At present, the implementation of the thesis trial evaluation at the Information Technology Faculty of the Islamic University of Kalimantan Muhammad Arsyad Al Banjari Banjarmasin is still manual, where when the presentation of proposals and panelists thesis examinations or examiners are given an assessment form using paper media. This assessment form is then recapitulated into a spreadsheet form the results are announced to students. This is less effective, especially when many students take thesis courses. For this reason, in this study, a thesis evaluation information system was created, to help all stages of the thesis evaluation process. To facilitate the accessibility of the system made web-based and integrated with existing academic systems. From the test results concluded, the system can run by the design and reports produced by the system following the processes that are running now.